Determinan terhadap Keputusan Pergantian Kantor Akuntan Publik Pada Perusahaan Manufaktur di Indonesia Tahun 2020-2024 - Dany Mahendra Hardjo; Achmad Badjuri (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2026)
The purpose of this study is to analyze the effect of management turnover, public accounting firm size, audit opinion, audit fee, and financial distress on auditor turnover. The sample used in this study was 285 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The analysis technique used in this study was logistic regression, and the results showed that company size has a significant positive effect on audit firm turnover (H1 is accepted), management turnover has a positive effect on audit firm turnover, but it is not significant, audit firm size has a significant positive effect on audit firm turnover, audit opinion has a positive effect on audit firm turnover but it is not significant, audit fees have a positive effect on audit firm turnover but it is not significant, financial distress has a positive effect on audit firm turnover but it is not significant